An Important Biomarker in Patients with Bell's Palsy: Serum Calprotectin - Turker, Cihan; Emre, Elif; Aydin, Suleyman; Dalgic, Mustafa; Baklaci, Deniz (Mdpi, 2025)
Background and Objectives: This study aimed to examine the relationship between serum calprotectin levels and facial paralysis in patients with Bell's palsy and to determine its prognostic significance. Materials and Methods: This study included 40 patients diagnosed with Bell's palsy and 20 healthy individuals as controls. The patients were categorized into three groups based on their response to treatment: complete response, partial response, and no response. Blood samples were taken before treatment and in the third month after treatment to measure C-reactive protein, white blood cell count, lymphocyte count, neutrophil count, neutrophil-to-lymphocyte ratio, and calprotectin levels. Results: Serum calprotectin levels were found to be elevated in patients with BP compared to the healthy controls; however, no significant correlation was observed between calprotectin levels and disease prognosis. Conclusions: The findings suggest that Bell's palsy patients have elevated serum calprotectin levels compared to healthy individuals, indicating the potential use of calprotectin as a biomarker in Bell's palsy. However, no significant difference in calprotectin levels was observed between patients with varying degrees of treatment response, suggesting that calprotectin may be limited in predicting disease prognosis.
Keywords: Bell's palsy; calprotectin; marker